Home again - McCoy, Shirlee (McCoy, Shirlee. Bradshaw brothers., 2018)
It<U+2019>s ex-Navy SEAL Porter Bradshaw<U+2019>s toughest challenge ever<U+2014>six grieving nieces and nephews. With his brother, Matthias, killed in a car crash, and his sister-in-law, Sunday, hospitalized, Porter must take his turn looking after their children and the ancestral farm. He doesn't know much about parenting. Still, Porter is used to going it alone professionally<U+2014>and personally. But warm-hearted teacher Clementine Warren is a complication he can<U+2019>t resist . . . For Clementine, Benevolence is where her hopes for a real home and family crashed and burned. But as Sunday's friend and former neighbor, she promised to always be there for the children. And as she and Porter work to comfort the young Bradshaws, his sense of duty and passionate commitment are rekindling more than Clementine<U+2019>s dreams. Now with trouble coming, she'll face down her fears to prove to Porter, and herself, that together they can make a future full of love . . .